Seasonal Evolution of Cape Darnley Bottom Water Revealed by Mooring Measurements - Mizuta, Genta; Fukamachi, Yasushi; Simizu, Daisuke; Matsumura, Yoshimasa; Kitade, Yujiro; Hirano, Daisuke; Fujii, Masakazu; Nogi, Yoshifumi; Ohshima, Kay I. (Frontiers in Marine Science, 2021)
This study examines the seasonal evolution of Cape Darnley Bottom Water (CDBW), using the results of mooring and hydrographic measurements in the slope region off Cape Darnley in 2008–2009 and 2013–2014. Newly formed CDBW began reaching the western and nearshore part of the slope region off Cape Darnley in April, spread to the offshore and eastern part in May, and reached the easternmost part in September. The potential temperature and salinity decreased and the neutral density increased when newly formed CDBW reached mooring sites. Potential temperature-salinity properties of CDBW changed over time and location. The salinity of the source water of CDBW estimated from potential temperature-salinity diagrams started to increase at a nearshore mooring in late April, which is about 2 months after the onset of sea-ice production, and continued to increase during the ice production season. It is most probable that the accumulation of brine in the Cape Darnley polynya produces the seasonal variation of potential temperature-salinity properties of CDBW. Two types of CDBW were identified. Cold and less saline CDBW and warm and saline CDBW were present in Wild and Daly Canyons, respectively. This indicates that the salinity of the source water of CDBW increased in the westward direction. CDBW exhibited short-term variability induced by baroclinic instability.